2023
DOI: 10.3390/medicina59030543
|View full text |Cite
|
Sign up to set email alerts
|

Basic Operative Tactics for Pulmonary Echinococcosis in the Era of Endostaplers and Energy Devices

Abstract: Human echinococcosis is a zoonotic infection caused by the larvae of the tapeworm species Echinococcus. The liver is the most common location for a primary echinococcosis. However, the parasite may bypass or spread from the liver to the lungs, causing primary or secondary pulmonary echinococcosis, respectively. Pulmonary echinococcosis is a clinically challenging condition in which anthelminthic regiments are important, but surgery has the central role in removing the cysts and preventing recurrences. Surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Casulli et al [ 16 ] presented a case of cerebral CE in a child, along with a comparative molecular analysis of the isolated cyst specimens from the patient and sheep from local farms. Bakinowska et al [ 17 ] reported the surgical treatment of three different cases of pulmonary echinococcosis. They demonstrated that simple small pulmonary echinococcal lesions could be excised using endostaplers.…”
Section: Discussionmentioning
confidence: 99%
“…Casulli et al [ 16 ] presented a case of cerebral CE in a child, along with a comparative molecular analysis of the isolated cyst specimens from the patient and sheep from local farms. Bakinowska et al [ 17 ] reported the surgical treatment of three different cases of pulmonary echinococcosis. They demonstrated that simple small pulmonary echinococcal lesions could be excised using endostaplers.…”
Section: Discussionmentioning
confidence: 99%
“…The most common localizations of HC are the liver and lungs, which account for up to 60-80 % of cases [7][8][9]. Despite the development of detailed diagnostic methods and surgical methods for hydatid cysts, early diagnosis remains difficult [10].…”
Section: ключевые слова: эхинококкоз легкие видеоассистированная тора...mentioning
confidence: 99%
“…Unfortunately, VATS may not be applicable in certain clinical settings. At first, in the preoperative period, we can note the difficulties in treating the residual cavity [8,15]. Second, if there's a fear of cystic fluid contamination of the chest cavity.…”
Section: оригинальные исследованияmentioning
confidence: 99%